Insect Management for Sweet Corn: ENY-472/IG158, rev. 9/2005 - Nuessly, Gregg S.; Webb, Susan E. (EDIS, 2005)
Foliar, ear and root feeding insects can routinely cause economic losses to sweet corn if left untreated. The most important pests of sweet corn in Florida are the fall armyworm, corn earworm, lesser cornstalk borer, cutworms, corn silk fly, cucumber beetles, aphids, and wireworms. Less common pests of sweet corn include grasshoppers, corn blotch leafminer, twospotted spider mites, sap beetles, stink bugs, maize weevils and billbugs, white grubs, and white fringed beetles. This document is ENY-472 (which replaces ENY-449), one of a series of the Department of Entomology and Nematology, UF/IFAS Extension. Original publication date November 2001. Revised September 2005. ENY-472/IG158: Insect Management for Sweet Corn (ufl.edu)